Proven pulmonary aspergillosis in a COVID-19 patient: A case report - Khodavaisy, Sadegh; Khajavirad, Nasim; Hashemi, Seyed Jamal; Izadi, Alireza; Dehghan Manshadi, Seyed Ali; Abdollahi, Alireza; Aliramezani, Amir; Sasani, Elahe; Abdorahim, Mahsa; Kiyaeie, Reyhaneh Sadat; Khosravany, Zohre; Ibrahim Getso, Muhammad; et al. (Current medical mycology, 2021)
Background and Purpose: Coronavirus disease 2019 (COVID-19) has become a significant clinical challenge in healthcare settings all over the world. Critically ill COVID-19 patients with acute respiratory distress syndrome may be at increased risk of co-infection with pulmonary aspergillosis. This study aimed to describe a clinical case of proven pulmonary aspergillosis caused by Aspergillus tubingensis in a 59-year-old man with a history of hospitalization due to COVID-19 infection. Case report: The Covid-19 infection was confirmed by positive nasopharyngeal polymerase chain reaction. He had a cavitary lesion measured 20 mm in diameter with intracavitary soft tissue density in the left lung in the first chest computerized tomography scan. After 25 days, he showed two cavitary lesions in both lungs which raised suspicion of fungal infection; hence, the patient underwent a trans-thoracic biopsy of the cavitary lesion. The direct examination and culture of the biopsy material revealed Aspergillus species. To confirm the Aspergillus species identification, the beta-tubulin region was sequenced. The patient was treated with oral voriconazole. Conclusion: This report underlined the importance of early diagnosis and management of invasive fungal infections in severe COVID-19 patients